Prototype Website Monitoring Parameter Energi Listrik pada Gedung A, B, C, D, & I di UK PETRA - Gavriel Emmanuel Victorious; Lily Puspa Dewi; Resmana Lim (Universitas Kristen Petra, 2022)
In this modern era, technology is developing very quickly which can facilitate human needs. The fast developed technology need more energy resources such as electricity. This thesis is intended to display electrical energy parameter in the Petra Christian Building via website to show the energy consumption patterns. The data processing method is carried out using PHP on the website. Predictive data analysis using data from Petra Christian University Building which is sent via Gateway to WiFi/LAN. The result of the thesis shows that, the result of the data pattern can help provide an understanding of the pattern of electricity consumption in each building. The regression prediction result has a slope of about -0.75% from the original data. The survey result has an overall rating of 4,375 out of 5 which indicates that users are satisfied with this website.